Interactions between Climate and Trade Policies: A Survey - Marzio Galeotti; Claudia Kemfert (Fondazione Eni Enrico Mattei (FEEM), 2004)
Economic globalization affects the environment and sustainable development in several ways and through various channels. The purpose of this paper is to review the key links between globalization and the environment. The paper intends to consider the major issues in multilateral economic agreements in trade and finance that affect environmental sustainability. Major policy issues addressed by these agreements are considered from the perspective of trade liberalization, international investment and finance, and technology diffusion. The concept of trade reflected here is thus broader than international exchange of goods and services.
Keywords: H23; O33; Q01; Q25; Q28; 330; International climate policy; Sustainable development; Technical change; Klimaschutz; Handelsliberalisierung; Nachhaltige Entwicklung; Technischer Fortschritt; Umweltabkommen; WTO-Recht; Welt